Identification of WUSCHEL-related homeobox gene and truncated small peptides in transformation efficiency improvement in Eucalyptus - Zhuo-Ao Zhang; Mei-Ying Liu; Shu-Ning Ren; Xiao Liu; Yue-Hao Gao; Chen-Yu Zhu; Hao-Qiang Niu; Bo-Wen Chen; Chao Liu; Weilun Yin; Hou-Ling Wang; Xinli Xia (BMC Plant Biology, 2023)
Abstract Background The WUSCHEL-related Homeobox (WOX) genes, which encode plant-specific homeobox (HB) transcription factors, play crucial roles in regulating plant growth and development. However, the functions of WOX genes are little known in Eucalyptus, one of the fastest-growing tree resources with considerable widespread cultivation worldwide. Results A total of nine WOX genes named EgWOX1-EgWOX9 were retrieved and designated from Eucalyptus grandis. From the three divided clades marked as Modern/WUS, Intermediate and Ancient, the largest group Modern/WUS (6 EgWOXs) contains a specific domain with 8 amino acids: TLQLFPLR. The collinearity, cis-regulatory elements, protein-protein interaction network and gene expression analysis reveal that the WUS proteins in E. grandis involve in regulating meristems development and regeneration. Furthermore, by externally adding of truncated peptides isolated from WUS specific domain, the transformation efficiency in E. urophylla × E. grandis DH32-29 was significant enhanced. The transcriptomics data further reveals that the use of small peptides activates metabolism pathways such as starch and sucrose metabolism, phenylpropanoid biosynthesis and flavonoid biosynthesis. Conclusions Peptides isolated from WUS protein can be utilized to enhance the transformation efficiency in Eucalyptus, thereby contributing to the high-efficiency breeding of Eucalyptus.